1994
DOI: 10.1016/0735-1097(94)90001-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neurohumoral activation in patients with an acute myocardial infarction: Effect of captopril

Abstract: Neurohumoral activation at the time of hospital discharge in postinfarction patients is an independent sign of poor prognosis. This is particularly true for plasma renin activity and atrial natriuretic peptide. Except for 1-year cardiovascular mortality, captopril does not significantly modify these relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
3
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(158 citation statements)
references
References 25 publications
9
143
3
1
Order By: Relevance
“…Statistical analysis of BP changes from baseline was performed using a mixed-effect model with treatment (aliskiren or irbesartan) and day (14,29,57,85) as fixed factors, and subject (nested in treatment) as a random factor. The number of patients with overall control of BP (defined as o135/85 mm Hg) was analysed using a logistic regression model with treatment as a fixed factor and baseline msSBP and msDBP as covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis of BP changes from baseline was performed using a mixed-effect model with treatment (aliskiren or irbesartan) and day (14,29,57,85) as fixed factors, and subject (nested in treatment) as a random factor. The number of patients with overall control of BP (defined as o135/85 mm Hg) was analysed using a logistic regression model with treatment as a fixed factor and baseline msSBP and msDBP as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…11 Several studies have shown an association of elevated PRA with an increased risk of cardiovascular events. [12][13][14] Given the importance of RAAS overactivation in metabolic disorders, direct renin inhibition may be of particular benefit for patients with metabolic syndrome. Previous studies have shown that aliskiren-based treatment is superior to thiazide diuretic treatment for BP control in patients with hypertension and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In the SAVE trial, elevated plasma renin activity predicted a moderate increase in efficacy of captopril in reducing 1-year but not total cardiovascular mortality rates. 21 Enalapril offered a greater survival benefit in those with more markedly increased NE and renin levels in the Veterans Administration Heart Failure Trial II (V-HeFT II). 4 The relation of neurohormonal status to treatment effect on rates of worsening heart failure was not addressed in the latter report.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown, for example, in patients with congestive heart failure, in which indirect and direct markers of systemic and regional sympathetic drive (venous plasma norepinephrine, heart rate variability, heart rate spectral power, cardiac and renal norepinephrine spillover) have been documented to bear a close and direct relationship with cardiovascular mortality, disease progression and arrhythmic events, including sudden death (46)(47)(48)(49)(50)(51). Similar conclusions have been drawn by assessing the prognostic values of plasma norepinephrine or heart rate variability in the post-stroke phase following an acute myocardial infarction or in patients with vasospastic angina (52)(53)(54)(55).…”
Section: Sympathetic Activation Cardiovascular Risk and Organ Damagementioning
confidence: 99%